Tingkat Partisipasi Pemilih Dalam Pemilihan Umum (Pemilu) Bupati Dan Wakil Bupati Kabupaten Mojokerto 2020 : Partisipasi Pemilih Dalam Pemilihan Umum - Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam Majapahit Mojokerto, Ahmad Hasan Afandi; Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam Majapahit Mojokerto, Suprapto; Prodi Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Majapahit, Dany Mustof (MAJAPAHIT POLICY, 2021)
The dynamics of the voting process during the COVID-19 pandemic, during the election in Mojokerto Regency, had an impact on the psychology of voters. Therefore, socialization is often done to increase voter participation. The election process which is quite strict with rules accompanied by the application of health protocols, in order to avoid high crowd levels, is a new method applied by the KPUD, but these rules can affect the level of voter participation. The formulation of the problem in this study is what factors affect the high voter turnout in elections in the midst of a pandemic. The purpose of this research is to determine the factors that influence the high participation. This study uses a theoretical approach to political participation as an activity intended to choose good government either directly or indirectly.This research method uses mixed research including library research methods by reviewing library and information sources including scientific articles, books, research reports, and news related to the theme of political volunteers and elections. The analyzed data relates to voter participation in elections; factors that influence voters during the pandemic in the 2020 Mojokerto Regency election, recap data manually and recap data online. The results of this study resulted in several findings including: 1) supporting factors and inhibiting factors. The supporting factors are dominated by the use of KPU social media and each candidate pair. 2) data on the number of voters, users of the right to vote including disabilities, and the votes acquired by pairs of candidates show: a) the comparison of the number of voters with users of voting rights: 78.66%; b) the ratio of the number of voters to users of the right to vote with disabilities: 41.82%; c) Comparison of votes between candidates, namely pair 1: 65.2%; b) couple 2: 15.4%; and c) partner 3: 19.4%.